Penerapan Sistem Informasi Akuntansi Penjualan Menggunakan Aplikasi Accurate Pada PT. VP Di Driyorejo - Febriani, Evi Pungky (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The purpose of this study was to analyze the application of the sales accounting information system at PT VP Galvalume in Driyorejo. Galvalume business is a business that provides many benefits, because development, especially in urban areas, will continue. Thus, making galvalume companies grow rapidly. The speed of this growth must be accompanied by an adequate information system to provide smooth operation and administration of the company. Technological advances in all fields including accounting information systems have made it easier for PT VP to manage their business. One form of progress in the accounting information system is the creation of an accounting application software that is accurate, using the accurate PT VP application can produce more accurate and timely financial reports. In its business operations, sales is one of the main activities carried out by the company. One of the determinants of a company's profit or loss in a certain period can be seen from its sales. In addition, sales also have a large enough risk for fraud to occur, so the company's management must take precautions. One way this can be done is to authorize each sale by an authorized department head. PT VP has carried out a structured sales process and each process has been authorized by the authorized department head. This study uses the method by interviewing several related parties, namely the Head of the HR Department of GA, the Head of the Marketing Department and the Head of the Accounting and Finance Department.